Studı Kualıtatıf Penerımaan M-Learnıng Bahasa Jepang Oleh Mahasıswa - Wiwie Sanjaya; Deli Deli (Universitas Internasional Batam, 2021)
Universitas Internasional Batam’s students who have interests in Japanese cultures facilitated by the existence of J-Club (Japanese Club). In J-Club, students sometimes gather to learn about Japanese language together. In this case, me as a researcher wants to do research about whether Japanese M-Learning can be accepted by J-Club members as their Japanese Learning media. This research is a qualitative study with Technology Acceptance Model (TAM). This research is done by interview and questionnaire. The result of this research is Japanese language M-Learning apparently can’t be fully well accepted. And the conclusion is that with TAM we can acknowledge that perceived usefulness and perceived ease of use variables take a big part of users’ satisfaction.